Environmental Risk Factors in Patients with Noninvasive Fungal Sinusitis - Badr Eldin Mostafa; Mohammed M. K. El Sharnoubi; Hesham A. A. El-Sersy; Mohammed S. M. Mahmoud (Scientifica)
Objective. The aim of our study was to try to determine the possible environmental risk factors for noninvasive fungal sinusitis in Egyptian patients. Methods. This is a prospective epidemiological case control study on the environmental risk factors of noninvasive fungal sinusitis. It included 60 patients and 100 age and sex matched controls. Results. There was a statistically significant relation between apartment floor, surface area, exposure to dust, exposure to cockroaches, poor air conditioning, and fungal sinusitis. Yet, no statistical significance was found between allergy related occupations, exposure to animals or plants, although their percentages were higher among cases, smoking, and urban or rural residence. Conclusion. We suggest that for patients with noninvasive fungal sinusitis a change in their living environment must be implied with better exposure to sunlight, larger well ventilated homes, proper cleaning of dust and cockroach extermination, and if possible the judicious use of air conditioners.